Effect of Steering Wheel Vibration on drivers Hands in a Two-Wheel Drivers Hand tractor (Journal of Engineering, 2011)
The paper presents research results of the vibration transmitted from the steering wheel of thetractor with a 2-wheel drive to the driver’s hands. The vibration measurements were carried out on thetractor randomly chosen from the collage of agriculture / university of Baghdad. Before testing thetractor was examined and adjusted following the producer’s recommendations. The vibration levelswere measured during the operation tillage at idling and at full load .The field was 3١٫٧ m above levelsea. Soil was treated at soil constant moisture (1٧-20 %) with depth of plowing (١٧ cm). Duringoperation the weather temperature was measured (15 C) and humidity was ( 27 % ) The vibration levelon the steering wheel was measured and analyzed .The frequency-weighted acceleration(RMS) , givenin m/ sec2 , was calculated. The vibration total value was defined as the root-mean-square of the threecomponent value.